Environmental and genetic factors affecting the weaning-estrus interval in sows - Leite, C. D. S.; Lui, J. F. [UNESP]; Albuquerque, Lucia Galvão de [UNESP]; Alves, D. N. M. (Funpec-editora, 2011)
We examined the effects of environmental and genetic factors on the weaning-to-estrus interval (WEI) in sows. In order to perform the analyses of the environmental factors, 8104 observations of the 1st to the 6th WEI were carried out, while 6548 observations of the 1st to the 3rd WEI were carried out for the analyses of genetic factors. The environmental model included as fixed effects, herd, genetic line, year and season of birth, as well as the covariates, age of sow at farrowing, litter size at birth and lactation length. Genetic analysis was performed by repeatability and multitrait models. The mean and coefficient of variation for WEI were 7.02 days and 100.6%, respectively. The linear effect of lactation length and the quadratic effect of the age of sow at farrowing affected the WEI. Herd, year and season of farrowing were significant sources of variation for WEI, and there was no influence of genetic line or of litter size at birth. Heritability estimated by the repeatability model was 0.04, while heritabilities obtained by the multitrait model were 0.07, 0.02 and 0.07 for the first three WEI, respectively. Estimates of genetic correlations among the different WEI were of moderate to low magnitude. It was concluded that environmental factors, such as year and season of farrowing, lactation length, age of sow at farrowing and herd, should be considered in the model for best estimation of genetic parameters for this trait. Although with only a small possible genetic gain, selection can be made based on the first WEI.
Keywords: repeatability; Multitrait model; Non-genetic factors; Heritability